2017
DOI: 10.1111/gcb.13898
|View full text |Cite
|
Sign up to set email alerts
|

Large soil organic carbon increase due to improved agronomic management in the North China Plain from 1980s to 2010s

Abstract: Agricultural soils are widely recognized to be capable of carbon sequestration that contributes to mitigating CO emissions. To better understand soil organic carbon (SOC) stock dynamics and its driving and controlling factors corresponding with a period of rapid agronomic evolution from the 1980s to the 2010s in the North China Plain (NCP), we collected data from two region-wide soil sampling campaigns (in the 1980s and 2010s) and conducted an analysis of the controlling factors using the random forest model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 70 publications
2
44
1
Order By: Relevance
“…This suggests that the overall trend of subsoil SOC decreases has existed since the 1980s. Similarly, although some studies found overall trends of SOC increase in the 20–40 cm soil layer in other agricultural districts of China, their results also indicated that the SOC content of the 20–40 cm soil layer decreased in some subareas or soil types (Han et al, 2017; Yan et al, 2011). Compared with previous studies, we further found that the largest SOC decrease occurred in the 40–60 cm soil layer.…”
Section: Discussionmentioning
confidence: 94%
“…This suggests that the overall trend of subsoil SOC decreases has existed since the 1980s. Similarly, although some studies found overall trends of SOC increase in the 20–40 cm soil layer in other agricultural districts of China, their results also indicated that the SOC content of the 20–40 cm soil layer decreased in some subareas or soil types (Han et al, 2017; Yan et al, 2011). Compared with previous studies, we further found that the largest SOC decrease occurred in the 40–60 cm soil layer.…”
Section: Discussionmentioning
confidence: 94%
“…The North China Plain (NCP) plays an indispensable role in China's food provision, accounting for 32% of national grain production in 2015. Soils in the NCP are historically known to be low in fertility [18], which is a major challenge for crop production in this region. The low SOC (soil organic carbon) content is mainly due to the burning of crop straw after harvest and the insufficient application of organic manure.…”
Section: Introductionmentioning
confidence: 99%
“…The emergy of topsoil loss was calculated using soil organic carbon (SOC) concentration [29]. Thus, the factor of topsoil loss from the E L was canceled out as the SOC concentration of the entire North China Plain increased over the past 30 years under conventional tillage methods [30]. Three years of local SOC data from the Yucheng Comprehensive Experiment Station also verified this trend (Supplementary Material D).…”
Section: Emergy Analysismentioning
confidence: 89%